Therapeutic Implications of Menin Inhibitors in the Treatment of Acute Leukemia: A Critical Review - Martina Canichella; Cristina Papayannidis; Carla Mazzone; Paolo de Fabritiis (Diseases, 2025)
Menin inhibitors are a class of targeted agents that exemplify how a deeper understanding of leukemia pathogenesis can unify seemingly distinct genetic acute leukemia subgroups under a common therapeutic strategy. In particular, acute leukemia with NPM1 mutations (NPM1m) and KMT2A rearrangements (KMT2Ar) represent the primary targets of this emerging drug class. Acute myeloid leukemia (AML) with NPM1m—which accounts for approximately 30% of AML cases and AML or acute lymphoblastic leukemia (ALL) with KMT2Ar—and is present in 5–10% of cases, shares a common pathogenetic mechanism: the aberrant activation of the MEIS1–HOXA axis. These leukemic subsets are associated with poor prognosis, particularly in the relapsed/refractory (R/R) setting. For KMT2Ar AML, the prognosis is especially dismal, with a median overall survival (OS) of 2.4 months and a complete remission (CR) rate of only 5%. In NPM1m AML, intensive chemotherapy achieves remission in approximately 80% of cases, but relapse remains a major challenge, occurring in nearly 50% of patients. Relapsed NPM1m AML is linked to a poor prognosis, with a median OS of 6.1 months (12-month OS: 30%) and a median relapse-free survival (RFS) of 5.5 months (12-month RFS: 34%). Menin inhibitors directly target the leukemogenic transcriptional program driven by HOX and MEIS1, disrupting oncogenic signaling and offering a promising therapeutic approach for these high-risk patients. This class of agents has rapidly progressed through clinical development, showing promising antileukemic activity in both treatment-naïve and R/R AML. Currently, six menin inhibitors are in clinical evaluation as monotherapy or in combination regimens: revumenib, ziftomenib, bleximenib (previously JNJ-75276617), enzomenib (previously DSP-5336), DS-1594, and BMF-219. In this review, we critically analyze the clinical development and therapeutic potential of the four most extensively studied menin inhibitors—revumenib, ziftomenib, bleximenib, and enzomenib. We discuss their efficacy, safety profiles, and potential roles within the current treatment algorithm. The continued clinical evaluation of menin inhibitors may redefine treatment paradigms for NPM1m and KMT2Ar AML and other acute leukemia with the aberrant MEIS1-HOXA axis, offering new hope for patients with limited therapeutic options.